Labor Relations in the Conditions of Digitization of The Economy - V. M. Svistunov; V. V. Lobachev (Управление)
The article analyses modern tendencies of development of the digital economy, given their role in the development of society and, as a consequence, in the transformation of socio-economic relations. The goal is to identify the main directions of training in the digital environment. It is shown that in addition to training professionals in the IT industry is required a high-quality training in the field of management, i.e. in the area of systems-organization of interaction of the ecosystem of people and machines, where routine operations will be done by machines, intelligent control and regulatory function management.